RAV6N3, Message from the Editor-in-chief (September - December 2016) - Castro Borges, Pedro (Revista ALCONPAT, 2016)
Latin American Journal on Quality Control, Pathology, and the Recuperation of Construction www.revistaalconpat.org It is gratifying for the team of the ALCONPAT Journal to see the second issue of our sixth year published. The purpose of the ALCONPAT (RA) Journal is to publish case studies related to the topics of our association, such as quality control, pathology, and the recuperation of constructions, all the while motivating the presentation of basic or applied researches, revisions, or documental researches. This edition V6N3 begins with a work from Brazil, in which Carlos Welligton Pires Sobrinho y Antonio Carlos Costa, they talk about the effects of applying badly designed repair techniques in 1981, which, together with the absence of preventive maintenance, leaks and even the growth of shrubs embedded in the masonry, led to the instability of the bell towers of the Basilica of the Church of Penha The authors present and discuss the historical, current situation, techniques and original strategies used in the development of structural reinforcement design of both bell towers of the Basilica of the Penha Church. The second work, from Argentina, by Jorge Daniel Sota et. al., present a work on the determination of the degree of maturity of concrete in situ in a structure. Their results allow to determine the curve of maturity of the concrete studied and to establish the degree of maturity in each of the differentiated parts of the structure. The use of this methodology and equipment allows to control the totality of the received concrete, its homogeneity and to monitor its resistance in real time. In the third article, from Brazil, Gustavo Macioski et. al., they analyze how the steel type, pH of the medium and the surface protection of the steel bar can change the electrochemical properties of this metal. For this, they apply the linear polarization resistance technique on steel bars to evaluate the corrosion of the samples. The study evaluated the CA-50, CA-60 and CP-175-RB steels, with or without surface protection. From the results it is possible to observe how the three variables influence the results of the current density and corrosion rate. The fourth article by Jennifer A. Canul et al., is from Mexico. The authors analyze the concrete made with crushed limestone of high absorption (ACTAA) from Yucatan, Mexico, which is considered of low quality. Their results indicated that the CV can be used in concrete with ACTAA as a fine inert aggregate since it manages to maintain a compressive strength like the reference. Equations are presented for the prediction of mechanical properties. The fifth work in this issue is from Mexico, by Trinidad Pére et al., the influence of Inconel 182 as buttering material in the mechanical properties of dissimilar metal welds between plain carbon steel and stainless-steel bars welded using SMAW has been investigated by using microstructural analysis, very common in field welding for construction. Their results indicated that even if the joints contain defects generated by the welder, the mechanical properties of dissimilar welded joint without buttering are higher than the properties of joints with buttering. The sixth article, of documentary research, is from Brazil, in which B. Fernandes et al. contribute to contribute to the analysis of non-conformity concrete, focusing on long time effects. A review of compressive strength evolution, results variability and acceptance criteria was made. In addition, it is presented a case study of a nonconforming concrete used in composite structures (concrete-filled steel columns) that present 28 days strength below the specified. This analysis, associated with a revision of the structural design and a carefully assessment, could help decision taking in case of non-conformity concretes. The seventh work is by Yolanda Hernández et. al, from Venezuela, they investigate an empirical correlation between the rebar corrosion rate and the corrosion-induced crack width propagation rate produced on beam’s concrete cover, with or without load application to these beams. The results showed a direct relation between crack width propagation and rebar corrosion rate, showing wider cracks in the loaded beams. The closing article is by Diego Jesus de Souza et al., from Brazil, they evaluate the possibility of negotiating corporate real estate, considering the expectations of users of real estate companies. Thus, the purchase opportunities and its alternatives were evaluated: the purchase of property, short-term rentals, long-term rental, custom construction and durability. The result of the analysis is the recommendation of possible choices between the shown alternatives, starting from the one that best meets the criteria prioritized by stakeholders. The ALCONPAT journal recently was described by CONACYT as competent at international level, obtaining a higher score than other journals of its classification in Q4 and Q3 of Scopus and ISI. http://www.revistascytconacyt.mx/index.php/revistas/resultado/385 By the Editorial Board Pedro Castro Borges Editor-in-chief